Pemberitaan Kasus Prostitusi Online Vanessa Angel di Media Makassar.tribunnews.com - Ulfa Mawaddah Afriliani; Sri Budi Lestari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is motivated by the writer's interest in Vanessa Angel who was involved in an online prostitution case, the report that released in the media about her in that case raised gender-biased coverage, most of the time it get out of the context of the problem, and one of the media that actively contributed to this was Makassar.tribunnews.com. In this study, the authors chose eight gender-biased articles published by Makassar.tribunnews.com in the period of time from January 6, 2019, to January 31, 2019, which were then analyzed using the Sara Mills critical discourse analysis method consisting of subject-object position and writer-reader position. The step is used to find out how Vanessa is displayed in the text, both in the form of photos or in the news. From the results of the analysis, the author sees that the reporter in writing the case article, positions himself as a narrator who has full authority in directing the course of events, therefore Vanessa as a woman who is at once a celebrity is displayed as a negative character in this case. Besides, she was also positioned as a party objectified by a journalist. This can be seen from the way journalist choose their sources, photos, highlight the context of bias, and the selection of some sentences that emphasize Vanessa as the agent of the problem. The patriarchal ideology, which became the dominant ideology in this media, can also be seen from the battle in the editorial room of Makassar.tribunnews.com which has a greater number of male crews, so often the articles released are also edited by men. The thick position and portion of men's work in this media editor, ultimately also makes the patriarchal perspective dominate the narrative text reporting on the Vanessa case so that it leads to gender bias.